2022
DOI: 10.6007/ijarped/v11-i3/14722
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Effectiveness of Social Media in Improving Speaking Skills of ESL Learners

Abstract: The Ministry of Education (MOE) has traditionally placed a strong emphasis on both the teaching and learning of English as a second language by its learners. It is crucial for the Malaysians as a second language users of English to improve their language skills especially speaking skills as it enables language users to be very much involved in verbal communication for the motive of providing and exchanging information as well as establishing long term bonding. Acquiring better speaking knowledge presents a sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The findings also reveal that students follow foreign English Language teachers online and make use of various social media sites such as You Tube to watch English Language tutorials (Ilyas & Putri, 2020). It is through the use of these social media sites that students strongly attest to the fact that they have ameliorated their productive skills (Bicen et al, 2015;Manogaran & Sulaiman, 2022). Furthermore, Vikneswaran & Krish (2016), Mitu (2020) and Zhou (2021) affirm that digital social media can enhance students' communicative competence if utilised properly.…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…The findings also reveal that students follow foreign English Language teachers online and make use of various social media sites such as You Tube to watch English Language tutorials (Ilyas & Putri, 2020). It is through the use of these social media sites that students strongly attest to the fact that they have ameliorated their productive skills (Bicen et al, 2015;Manogaran & Sulaiman, 2022). Furthermore, Vikneswaran & Krish (2016), Mitu (2020) and Zhou (2021) affirm that digital social media can enhance students' communicative competence if utilised properly.…”
Section: Literature Reviewmentioning
confidence: 88%
“…This is because findings from Belal (2014), (Florence, 2018), Nkhi (2018), Ghouali & Benmoussat (2019) and Songxaba & Sincuba (2019) on the one hand reveal that social media has a negative impact on students' grammatical competence because of the informal language used therein. On the other hand however, findings from Bicen et al (2015), Vikneswaran & Krish (2016), Mitu (2020), Zhou (2021), Ilyas &Putri (2020), andManogaran &Sulaiman (2022) revealed that it is through the use of these social media sites that students strongly attest to the fact that they have ameliorated their productive skills. Furthermore, the authors affirm that digital social media can enhance students' communicative competence if utilized properly.…”
Section: Discussionmentioning
confidence: 99%